Who bears interest rate risk? - Peter Hoffmann; Sam Langfield; Federico Pierobon; Guillaume Vuillemey (European Central Bank (ECB), 2018)
We study the allocation of interest rate risk within the European banking sector using novel data. Banks' exposure to interest rate risk is small on aggregate, but heterogeneous in the cross-section. In contrast to conventional wisdom, net worth is increasing in interest rates for approximately half of the institutions in our sample. Cross-sectional variation in banks' exposures is driven by cross-country differences in loan-rate fixation conventions for mortgages. Banks use derivatives to partially hedge on-balance sheet exposures. Residual exposures imply that changes in interest rates have redistributive effects within the banking sector.
Keywords: G21; E43; E44; 330; interest rate risk; banking; risk management; hedging